Putative and pretreatment drug resistance mutations in reverse transcriptase gene among untreated chronic hepatitis B patients at Arifin Achmad Regional District Hospital, Riau, Indonesia - Arfianti Arfianti; Fauzia Andrini Djojosugito; Maisaroh Maisaroh; Hendra Asputra; Dita Kartika Sari; Tubagus Odih Rhomdani Wahid (Acta Biochimica Indonesiana, 2022)
Background: Mutations within the hepatitis B virus (HBV) reverse transcriptase (RT) gene have been associated with drug resistance against nucleos(t)ide analogs (NAs). Objective: This study aimed to identify mutations in the RT gene among patients with chronic hepatitis B (CHB) before receiving antiviral therapy and its relationship with the HBV genotypes. Methods: A total of 26 HBV DNA was extracted from the blood plasma of CHB patients. HBV RT gene was amplified and sequenced using the Sanger dideoxy sequencing method. The HBV genotype was determined through phylogenetic analysis using the Maximum Likelihood method. Results: The study subjects comprised 14 CHB patients without complications and 12 CHB patients with cirrhosis/hepatoma. CHB patients with cirrhosis/hepatoma were older than those without complications. The HBV genotypes comprised 15 (57.7%) genotype C and 11 (42.3%) genotype B. All treatment-naïve CHB patients did not demonstrate any classical NA resistance mutations within the RT gene. However, several putative and pretreatment resistance mutations, including F221Y, N238H, and V224I, were high frequency in more than 40% of study subjects. In addition, F221Y and N238H/Q mutations were frequently observed in genotype B, while V224 I was only found in patients infected with genotype C (p=0.000). Conclusions: There was no evidence of classical RT gene mutations associated with NA resistance in treatment-naïve patients with CHB. However, several putative and pretreatment mutations were identified as genotype-specific mutations and may contribute to antiviral resistance against NAs.